Evaluation of internal medicine physicians' attitudes toward the treatment of dyslipidemia. Issue 6 (17th August 2020) - Kara, Emre; Tecen Yucel, Kamer; Bayraktar-Ekincioglu, Aygin; Demirkan, Kutay; Tokgozoglu, Lale; Unal, Serhat
ABSTRACT: Objectives : Dyslipidemia is one of the risk factors for atherosclerotic cardiovascular disease. Cardiovascular events decrease with decreasing LDL-C levels and all guidelines emphasize the importance of LDL-C lowering. However, implementation in real life is suboptimal. This study aimed to evaluate the treatment approaches to the dyslipidemia of physicians. Methods : This study was conducted as an online survey for internal medicine specialists and residents. The survey included questions on the physicians' demographics, their attitudes toward dyslipidemia management in three different case scenarios and questions. The physicians were asked to indicate their treatment and guideline preferences in the three cases. Results : Among the 366 participants 67.5% were internal medicine specialists and 18.9% were internal medicine residents. Fourteen percent of physicians did not use guidelines in clinical practice. Five percent of specialists and 10.1% of residents doubted the necessity of dyslipidemia treatment, 30% of both specialists and residents were affected by the patient's reluctance. The specialists were more likely to state that reaching the target LDL-C should be a priority compared to the residents (p = 0.003). Most physicians (58.7%) treated the patients according to the guideline recommendations if the patients were at high risk. They were less likely to get to guideline recommendation goals if the patients were at low risk (29.8%). Conclusion : Despite overwhelming evidence, some physicians did not use guidelines and some physicians doubted the necessity of dyslipidemia treatment. A significant proportion of physicians were affected by the patient's reluctance. There is a clear need to educate physicians about the importance of guidelines.